Introduction to the special issue: Student experience in Latin American higher education - Santelices, Maria Veronica; Celis, Sergio (Education Policy Analysis Archives, 2022)
In this introduction, the guest editors present an overview of the 11 articles that make up the special issue on student experience in Latin American higher education. The introduction provides context about the higher education sector in Latin America, draws attention to the main features of the articles, and highlights common themes across them. The guest editors also comment on the parallels and contrasts with the student experience discussed by the literature from other geographical locations. Based on the preparation and publication of the special issue, suggestions for further research are provided.